Implementation of Islamic Character Values Education in MIN 13 Pidie Jaya - Evarianti, Riza; Dhiauddin; Saifuddin (Kamara Journal, 2025)
Character crises and the degradation of adolescent moral values are the main concerns in the world of education. In Bandar Dua District, Pidie Jaya Regency, problems such as smoking in public places, skipping school, and bullying require early prevention. This study aims to analyze the application of Islamic character values and identify Islamic character values that are the focus of development in the educational process at MIN 13 Pidie Jaya. This study uses a descriptive qualitative approach with a research location at MIN 13 Pidie Jaya, Bandar Dua District, Pidie Jaya Regency. The main data sources are obtained from madrasah heads, curriculum coordinators, student coordinators, teachers, students, and related documents. The results of the study showed that Islamic character values were integrated through learning, madrasah culture, and routines such as Qur'an recitals, congregational prayers, joint prayers, reading Yasin on Fridays, sacrificial piggy banks, and religious extracurricular activities.